2012
DOI: 10.1074/jbc.m111.334722
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Leucine-Valine Change in Distinct Low pH Requirements for Membrane Fusion between Two Related Retrovirus Envelopes

Abstract: Background:The mechanism of viral membrane fusion is still poorly understood. Results: We show that a leucine-valine change in the JSRV and ENTV Env is responsible for their distinct low pH requirements for fusion. Conclusion: The Leu-Val change likely stabilizes an intermediate induced by receptor binding.Significance: This work represents a unique example whereby a simple Leu-Val change has critical impact on virus entry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
(37 reference statements)
1
13
0
Order By: Relevance
“…We performed metabolic labeling of 293T cells co-expressing IFITMs and JSRV Env, and determined shedding of JSRV SU in the presence or absence of a soluble form of Hyal2 (sHyal2). In our previous studies, we had established that shedding of JSRV SU into culture media is an important indicator of Hyal2 receptor-mediated triggering for the fusion activation of JSRV Env [28], [29], [30]. Here we observed that the levels of JSRV SU harvested from the culture media of 293T cells expressing IFITM1, 2 or 3 were comparable to those of parental cells, and that they all increased with the presence of sHyal2 in a dose-dependent manner (Fig.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…We performed metabolic labeling of 293T cells co-expressing IFITMs and JSRV Env, and determined shedding of JSRV SU in the presence or absence of a soluble form of Hyal2 (sHyal2). In our previous studies, we had established that shedding of JSRV SU into culture media is an important indicator of Hyal2 receptor-mediated triggering for the fusion activation of JSRV Env [28], [29], [30]. Here we observed that the levels of JSRV SU harvested from the culture media of 293T cells expressing IFITM1, 2 or 3 were comparable to those of parental cells, and that they all increased with the presence of sHyal2 in a dose-dependent manner (Fig.…”
Section: Resultssupporting
confidence: 58%
“…We chose the Jaagsiekte sheep retrovirus (JSRV) envelope (Env) and IAV hemagglutinin (HA) proteins as the model system of study because of some of their advantages. JSRV is a simple retrovirus, with Env-mediated membrane fusion and entry requiring both receptor-binding and low pH; an initial receptor binding primes the subsequent low pH-dependent conformational changes required for full activation [27], [28], [29], [30]. This unconventional two-step triggering mechanism was originally discovered in the avian sarcoma leukosis virus (ASLV) [31], and has now been suggested to operate in other enveloped viruses, including HCV [32].…”
Section: Introductionmentioning
confidence: 99%
“…Pseudovirion Production and Infection-GFP-encoding and alkaline phosphatase-encoding Moloney murine leukemia virus pseudovirions were produced as described previously (11,33). Lentiviral shRNA/AP-3 pseudotypes were generated according to the manufacturer's instructions (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…The experiments were performed as described (53,54). Briefly, 293T cells were transfected with plasmids encoding HIV-1 proviral DNAs or HIV-1 Gag, along with plasmids expressing TIMs or PS receptors.…”
Section: Methodsmentioning
confidence: 99%